Charge pump-based MOSFET-only 1.5-bit pipelined ADC stage in digital CMOS technology. Issue 10 (2nd October 2016) - Singh, Anil; Agarwal, Alpana
ABSTRACT: A simple low-power and low-area metal-oxide-semiconductor field-effect transistor-only fully differential 1.5-bit pipelined analog-to-digital converter stage is proposed and designed in Taiwan Semiconductor Manufacturing Company 0.18 μm-technology using BSIM3v3 parameters with supply voltage of 1.8 V in inexpensive digital complementary metal-oxide semiconductor (CMOS) technology. It is based on charge pump technique to achieve the desired voltage gain of 2, independent of capacitor mismatch and avoiding the need of power hungry operational amplifier-based architecture to reduce the power, Si area and cost. Various capacitances are implemented by metal-oxide semiconductor capacitors, offering compatibility with cheaper digital CMOS process in order to reduce the much required manufacturing cost.